2010
DOI: 10.1111/j.1476-5381.2010.00826.x
|View full text |Cite
|
Sign up to set email alerts
|

Emodin, a natural product, selectively inhibits 11β‐hydroxysteroid dehydrogenase type 1 and ameliorates metabolic disorder in diet‐induced obese mice

Abstract: BACKGROUND AND PURPOSE 11β‐Hydroxysteroid dehydrogenase type 1 (11β‐HSD1) is an attractive therapeutic target of type 2 diabetes and metabolic syndrome. Emodin, a natural product and active ingredient of various Chinese herbs, has been demonstrated to possess multiple biological activities. Here, we investigated the effects of emodin on 11β‐HSD1 and its ability to ameliorate metabolic disorders in diet‐induced obese (DIO) mice. EXPERIMENTAL APPROACH Scintillation proximity assay was performed to evaluate inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
91
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 115 publications
(95 citation statements)
references
References 55 publications
2
91
1
1
Order By: Relevance
“…Therefore, theoretically, the 11b-HSD1 inhibitor cannot attenuate the active GC-induced pathological changes. A previous study reported that an 11b-HSD1 inhibitor, emodin, could reverse prednisoneinduced insulin resistance in obese mice, but had no effect on dexamethasone induction (Feng et al 2010). Similar results were observed in the action of LG13.…”
Section: Figuresupporting
confidence: 74%
“…Therefore, theoretically, the 11b-HSD1 inhibitor cannot attenuate the active GC-induced pathological changes. A previous study reported that an 11b-HSD1 inhibitor, emodin, could reverse prednisoneinduced insulin resistance in obese mice, but had no effect on dexamethasone induction (Feng et al 2010). Similar results were observed in the action of LG13.…”
Section: Figuresupporting
confidence: 74%
“…It demonstrates a variety of biological activities, such as anti-virus activities, anti-tumor activities, anti-inflammatory activities, and immune suppression, and it can also serve as a potential agent in therapy for liver cirrhosis, diabetic nephropathy and atherosclerosis [15][16][17][18][19][20] . Our previous study showed that emodin is a potent and selective 11β-HSD1 inhibitor and can ameliorate metabolic disorders in diet-induced obese mice [21] . In the present study, we investigated the effect of emodin on adipocyte function and the underlying mechanisms involving inhibition of 11β-HSD1.…”
Section: Introductionmentioning
confidence: 99%
“…The 24 h ambulatory blood pressure measurements data (from the subset of patients who participated in ambulatory blood pressure measurements) suggest that MK-0736 has blood pressurelowering efficacy over a 24 h period not adequately represented by measuring sitting diastolic blood pressure and sitting systolic blood pressure, notably a greater blood pressure-lowering effect during daytime than during night-time (S. Shah et al, 2011). 11 -HSD1 inhibitors may improve a number of metabolic disturbances, unlike current available anti-diabetic compounds, that occur in obesity, T2DM and/or MetSyn patients, as seen from genetically engineered animal studies (Kotelevtsev et al, 1997;Morton et al, 2001;Morton et al, 2004) as well as from animal (Alberts et al, 2002;Alberts et al, 2003;Barf et al, 2002;Cooper & Stewart, 2009;Feng et al, 2010;Gathercole & Stewart, 2010;Hermanowski-Vosatka et al, 2005;Johansson et al, 2008;J. Liu et al, 2011;Livingstone & Walker, 2003;Morgan et al, 2009;Park et al, 2011;Taylor et al, 2008;Véniant et al, 2010;S.…”
Section: Human 11β-hsd1 Inhibition Studiesmentioning
confidence: 99%
“…Besides inhibition of 11 -HSD1 reductase activity, increase of 11 -HSD1 dehydrogenase (oxidase) activity, without inhibition of 11 -HSD2, may provide a better therapeutic strategy for T2DM, obesity and MetSyn (Ge et al, 2010). 11 -HSD1 is also inhibited by natural compounds, such as an active ingredient of various Chinese herbs (emodin), derivatives or analogues of the licorice root, coffee extract, flavanone (and the monohydroxylated flavonoid 2′-hydroxyflavanone), endogenous steroids and their metabolites and bile acids (Andrews et al, 2003;Atanasov et al, 2006;Chalbot & Morfin, 2006;Classen-Houben et al, 2009;Diederich et al, 2000;Feng et al, 2010;Gathercole & Stewart, 2010;Hollis & Huber, 2011;Latif et al, 2005;Livingstone & Walker, 2003;Maeda et al, 2010;Monder et al, 1989;Morris et al, 2004;Odermatt & Nashev, 2010;Sandeep et al, 2005;Schweizer et al, 2003;Su et al, 2007;Taylor et al, 2008;van Raalte et al, 2009;Walker et al, 1995a;Wamil & Seckl, 2007). Glycyrrhetinic acid, the active pharmacological ingredient of the licorice root and some of its derivatives, as well as its steroidal synthetic analogue carbenoxolone (hemisuccinate derivative of glycyrrhetinic acid) are inhibitors of both 11 -HSD1 and 11 -HSD2 (the magnitude of the effect being dependent on in vitro versus in vivo environment, dose, administration mode, tissue and specie as well as compound structure) (Abdallah et al, 2005;Andrews et al, 2003;Classen-Houben et al, 2009;Gathercole & Stewart, 2010;Hollis & Huber, 2011;Jellinck et al, 1993;Livingstone & Walker, 2003;Monder et al, 1989;Sandeep et al, 2005;Su et al, 2007;…”
Section: β-Hsd1 Inhibition Studiesmentioning
confidence: 99%